2017
DOI: 10.1080/19336918.2016.1264559
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A8 promotes VEGF-A driven endothelial cell sprouting

Abstract: The physiological and pathological process of angiogenesis relies on orchestrated endothelial cell (EC) adhesion, migration and formation of new vessels. Here we report that human umbilical vein endothelial cells (HUVECs) deficient in Annexin A8 (AnxA8), a member of the annexin family of Ca- and membrane binding proteins, are strongly deficient in their ability to sprout in response to vascular endothelial growth factor (VEGF)-A, and are strongly impaired in their ability to migrate and adhere to β1 integrin-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Finally, as VEGF signaling is knowingly involved in endothelial cell phenotype (Heitzig et al, ; Li et al, ), we decided evaluating VEGF (Figure a), VEGFR1 (Figure b), and VEGFR2 (Figure c) genes in response to mechanosignaling pathways. Specifically, our data show that although there is no effect on VEGF gene activation (Figure a), the both receptors were modified.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, as VEGF signaling is knowingly involved in endothelial cell phenotype (Heitzig et al, ; Li et al, ), we decided evaluating VEGF (Figure a), VEGFR1 (Figure b), and VEGFR2 (Figure c) genes in response to mechanosignaling pathways. Specifically, our data show that although there is no effect on VEGF gene activation (Figure a), the both receptors were modified.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that ANXA8 regulates leukocyte recruitment to activate endothelial cells and affects CD63 and p-selectin delivery [26]. Meanwhile, ANXA8 can organize the formation of CD63/ VEGFR2/b1 integrin complex and over-activate VEGF-A signal transduction pathway [27]. Furthermore, a previous study demonstrated that ANXA8 acts as a crux regulator of the endosomal regulation of cholesterol homeostasis, and this membrane binding is used to affect such a cytosolic regulatory protein dynamically [28].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, within the context of adipose tissue function, the unique affinity of AnxA8 towards phosphatidylinositides and F-actin relevant for membrane-cytoskeleton interactions, might be most important. In fact, these distinctive membrane- and actin-binding properties of AnxA8 affect the functioning of late endosomes [84,85] and in endothelial cells, this contributes to control the delivery of CD63 from late endocytic vesicles to the cell surface for leukocyte recruitment and migration [86,89]. In addition, AnxA8 is associated with cholesterol-rich late endosomes, and similarly to AnxA6 overexpression or NPC1 inhibition [19,31,63,64,72,73], AnxA8 depletion results in cholesterol accumulation in this compartment [87].…”
Section: Annexin Expression Patterns In Adipose Tissue and Their Pmentioning
confidence: 99%